Damage assessment of structures against blast load based on mode approximation method - Huang, Xin (2011)
Damage assessment plays an important role in the evaluation of the stability and strength of structures, which is significant for both the existing structures and those under construction. An effective damage assessment method based on the deformation behavior of a structure is essential in order to apply protective measures when there exists potential blast load risks. For a reinforced concrete structural element, the analysis becomes more complicated because the reinforced concrete always deforms in a nonlinear way, especially in the post-failure stage.